The essential norm of a composition operator mapping into Qk type spaces - Marko Kotilainen; Jouni Rättyä (Journal of Function Spaces and Applications)
An asymptotic formula for the essential norm of the composition operator Cφ(f):=f∘φ, induced by an analytic self-map φ of the unit disc, mapping from the α-Bloch space ℬα or the Dirichlet type space Dαp into Qk(p,q) is established in terms of an integral condition.